Highly efficient morpholine-based organocatalysts for the 1,4-addition reaction between aldehydes and nitroolefins: an unexploited class of catalysts - Vaghi, Francesco; Facchetti, Giorgio; Rimoldi, Isabella; Bottiglieri, Matteo; Contini, Alessandro; Gelmi, Maria Luisa; Bucci, Raffaella (Frontiers in Chemistry, 2023)
Many studies have demonstrated how the pyrrolidine nucleus is more efficient than the corresponding piperidine or morpholine as organocatalysts in the condensation of aldehydes with electrophiles via enamine. Focussing on morpholine–enamines, their low reactivity is ascribed to the presence of oxygen on the ring and to the pronounced pyramidalisation of nitrogen, decreasing the nucleophilicity of the enamine. Thus, the selection of efficient morpholine organocatalysts appears to be a difficult challenge. Herein, we reported on the synthesis of new organocatalysts belonging to the class of ß-morpholine amino acids that were tested in a model reaction, i.e., the 1,4-addition reaction of aldehydes to nitroolefins. Starting from commercially available amino acids and epichlorohydrin, we designed an efficient synthesis for the aforementioned catalysts, controlling the configuration and the substitution pattern. Computational studies indeed disclosed the transition state of the reaction, explaining why, despite all the limitations of the morpholine ring for enamine catalysis, our best catalyst works efficiently, affording condensation products with excellent yields, diastereoselection and good-to-exquisite enantioselectivity.